Business Consulting en la cadena de suministro de la línea de negocio postventa de International Camiones del Perú S.A. - Infantes Chávez, Melissa Elizabeth (2024)
This research presents the business consulting report for International Camiones del Perú S.A., the official distributor of the INTERNATIONAL® brand in the country. The company has experienced significant growth but faces challenges in managing its supply chain, particularly within the after-sales business line. Identifying operational deficiencies and proposing effective solutions to enhance performance is crucial. The report examines both internal and external factors affecting the company through an analysis of its strengths, weaknesses, opportunities, and threats. To gather relevant information, interviews were conducted with senior management, which allowed for the identification of critical areas and operational needs. From this diagnosis, it was determined that the primary issue lies in the lack of stock availability for high-rotation products, negatively impacting sales and increasing operational costs. Based on this finding, various potential solutions were evaluated using both qualitative and quantitative approaches. It is proposed that INTERPERÚ implement inventory management methodologies supported by technological tools that facilitate stock monitoring and control. Additionally, establishing a strategic framework that includes a Balanced Scorecard is recommended to align operations with business objectives. Finally, a plan for implementation is presented, aimed at generating a positive impact on the company's economic performance, supported by an analysis of the Net Present Value (NPV), thereby reinforcing the proposal to address the identified issue.